THE IMPACT OF ACTUATED CONTROL ON THE ENVIRONMENT AND THE TRAFFIC FLOW - Kalašová, Alica; Hájnik, Ambróz; Kubaľák, Stanislav; Beňuš, Ján; Harantová, Veronika (Journal of Applied Engineering Science, 2021)
In our paper, we have analyzed and compared fixed and actuated control at a chosen intersection, where we pointed out the importance of actuated control and its benefits. We have used traffic data from sensors in the roadway. The intersection was modelled in Aimsun, where we performed simulations. The research focused mainly on the impact of actuated control on the basic characteristics of the traffic flow, delay time and emissions. The outputs of simulations showed positive results of actuated control in all compared values. The environmental pollution topic is up-to-date and road transport has a significant impact on it. Furthermore, we want to continue with our research to investigate the impact of speed changes on emission production and the smoothness of the traffic flow under fixed and actuated control.
Keywords: intersection, delay time, emissions, simulation, fixed control, actuated control